Question and Answers Forum

All Questions      Topic List

None Questions

Previous in All Question      Next in All Question      

Previous in None      Next in None      

Question Number 27718 by mondodotto@gmail.com last updated on 13/Jan/18

Answered by prakash jain last updated on 13/Jan/18

((√(2+(√3))) )^x =a  ((√(2−(√3))) )^x =(1/a)  a+(1/a)=4⇒a^2 −4a+1=0  a=((4±(√(12)))/2)=2±(√3)  ((√(2+(√3))))^x =(2±(√3))  ((√(2+(√3))))^x =(2+(√3))⇒x=2  ((√(2+(√3))))^x =(2−(√3))⇒x=−2  x=±2

(2+3)x=a(23)x=1aa+1a=4a24a+1=0a=4±122=2±3(2+3)x=(2±3)(2+3)x=(2+3)x=2(2+3)x=(23)x=2x=±2

Commented by mondodotto@gmail.com last updated on 13/Jan/18

thanx a lot sir

thanxalotsir

Terms of Service

Privacy Policy

Contact: info@tinkutara.com